Core outcome sets in symptomatic peripheral artery disease, COS-PAD: Study protocol for developing core outcome sets in symptomatic PAD utilising systematic reviews, interviews, and delphi consensus. - Akam Shwan; Maria Gonzalez-Aguado; Rob D Sayers; John S M Houghton (PLoS ONE)
Background Symptomatic peripheral artery disease (PAD) presents as intermittent claudication or chronic limb-threatening ischaemia (CLTI). PAD research suffers from wide heterogeneity and non-comparability of outcome measures. The solution is to develop a core outcome set (COS) - a minimum standard of outcomes developed and agreed by key stakeholders (patients, healthcare professionals, and researchers). There are currently no agreed COSs for research in PAD. The aim of this project is to develop two separate COSs for symptomatic PAD; for each of intermittent claudication and CLTI. Methods/design The COSs will be developed according to Core Outcome Measures in Effectiveness Trials (COMET) guidelines. Two comprehensive systematic reviews will be supplemented by qualitative interviews of patients and carers and focus groups of healthcare professionals and researchers. A three-round Delphi consensus process followed by a stakeholder meeting will agree the final COSs. Full ethical approval has been granted by Health Research Authority, HRA and Health and Care Research Wales, HCRW (Brighton and Sussex REC reference 24/LO/0258). Conclusion Two separate core outcome sets for research involving patients with intermittent claudication and CLTI will be developed. This will aid study design and ensure meaningful results of clinical trials to guide patient management and development of best-practice guidelines for symptomatic PAD. Study registrations COMET registrations: 1590 and 2650.